ANALYSIS OF UNSIGNALIZED INTERSECTIONS: CASE STUDY OF THE INTERSECTION OF JALAN SUKARAJA WETAN, MAJALENGKA - Ghaida Tsauraya Nur Fatimah; Andri Irfan Rifa'i (LEADER: Civil Engineering and Architecture Journal, 2024)
Traffic signs are the main thing that is very important for road users; of course, they help in terms of safety and security for drivers. Unsignalized traffic signals at intersections have been identified as the most dangerous locations in traffic. Not only in other countries, Indonesia has also implemented traffic signs at intersections, especially on highways. This journal aims to analyze factors that increase the risk of traffic jams and are prone to morning, afternoon, and evening accidents at the intersection of Jalan Sukaraja Wetan-Kulon, Jatiwangi District, and Majalengka Regency. This research was located at an unsignaled intersection, precisely at the Sukaraja Wetan-Kulon intersection, Jatiwangi sub-district, Majalengka district. The method used in this journal is quantitative methods. The Sukaraja Wetan-Kulon intersection has four approaches; each approach has two lanes. The data was obtained from calculating traffic volume, which involved conducting a survey directly at the location, namely in the field for two days, and divided into two, namely total flow volume and flow volume of main roads and minor roads. The basic capacity (Co) obtained at the intersection of four Sukaraja Wetan-Kulon roads is 2/2 UD, which is 2900. At the junction of four, the level of service depends on the degree of saturation, which has been obtained from the traffic flow value divided by the load capacity. The conclusion from this research is that the data obtained in the chapter above shows that peak traffic flow occurs on Tuesdays in the afternoon period at 16.00-17.00 with a total traffic flow volume of 7818.2 pcs/hour. The capacity of the Jalan Simpang Empat Sukaraja Wetan-Kulon greatly influences the value of the degree of saturation.